Indigenous and Quilombo People in Higher Education: An analysis based on the UFGInclui Program - Marques, Kamila Evelyn Martins (2023)
The article presents an analysis of the profile of quota students, black quilombolas and indigenous people, who entered the Federal University of Catalão in 2020 by the UFG Inclui Program. Starting from a historical discussion on the racial and ethnic issue in Brazil, we present the program, its implementation and structure within the university and, finally, we present and analyze the data. The results express that even though the program has existed since 2008, there is a low demand in relation to the number of vacancies offered. We verified that most of the entrants are young, have specificities that are inherent to the juvenile condition, in addition to particularities about their territories and groups of origin, ways of life and educational background, showing that financial support is fundamental, however, the reception and recognition of these specificities by the institution is fundamental in the process of permanence, above all, demanding by an intercultural dialogue.